The quest for equity in Chile's higher education : decades of continued efforts - Catalán, Ximena, 1984-; Horn, Catherine L.; Santelices, María Verónica, 1974- (Lexington Books, 2019)
"This book studies three factors affecting equity in higher education outcomes for the Chilean case: the decision-making of students transitioning to higher education, the admission process, and the role of financial aid. It assesses how effective the combination of policies implemented has been at increasing access and leveling academic outcomes"--